2003
DOI: 10.5703/1288284313211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety Enforcement on Changing Driver Behavior - Runs on Red (1 of 2 Volumes)

Abstract: Prepared in cooperation with the Indiana Department of Transportation and Federal Highway Administration. AbstractRed light running (RLR) is a dangerous act. Approximately 22% of urban crashes at signalized intersections are caused nationwide by RLR. Nearly 1,036 deaths were caused nationwide by RLR in the year 2000. Indiana had no previous research conducted in this area; therefore, this research was aimed at estimating the RLR problem in Indiana. The other objectives of this research included: learning drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…According to an FHWA estimation (2), in 2001, about 200,000 crashes, 150,000 injuries, and 1,100 deaths were attributed to red light running. In Indiana, crash statistics for the 1997 to 1999 period showed that 22% of signalized intersection crashes were caused by red light running, which preceded 50% of fatal crashes at these intersections (3).…”
mentioning
confidence: 99%
“…According to an FHWA estimation (2), in 2001, about 200,000 crashes, 150,000 injuries, and 1,100 deaths were attributed to red light running. In Indiana, crash statistics for the 1997 to 1999 period showed that 22% of signalized intersection crashes were caused by red light running, which preceded 50% of fatal crashes at these intersections (3).…”
mentioning
confidence: 99%
“…Two methods can be used to extrapolate RLR violations from recorded video at an intersection (57). Although the RLRAP software package does not include a counting program similar to that used in the Purdue study, the goal of this project was to measure the accuracy of phase timing measurements and the repeatability of those measurements over multiple playbacks of the videotape (58).…”
Section: Discussionmentioning
confidence: 99%
“…Direct monitoring combined camera view (CTRE, Iowa State University).The machine-aided monitoring method's objective is to reduce the time needed to evaluate an approach with the sacrifice of minimal errors in the evaluation(57). As shown below inFigure 17, Purdue University researchers used Autoscope software to detected RLR vehicles at a single intersection approach while determining entering vehicle counts and approaching vehicle speeds.…”
mentioning
confidence: 99%
See 2 more Smart Citations